Therapeutic Perspective on Tardive Syndrome with Special Reference to Deep Brain Stimulation - Morigaki, Ryoma; Mure, Hideo; Kaji, Ryuji; Nagahiro, Shinji; Goto, Satoshi (Frontiers in Psychiatry, 2016)
Tardive syndrome (TDS) is a potentially permanent and irreversible hyperkinetic movement disorder caused by exposure to dopamine receptor blocking agents. Guidelines published by the American Academy of Neurology recommend pharmacological first-line treatment for TDS with clonazepam (level B), ginkgo biloba (level B), amantadine (level C), and tetrabenazine (level C). Recently, a Class II study provided level C evidence for use of deep brain stimulation (DBS) of the globus pallidus internus (GPi) in patients with TDS. Although the precise pathogenesis of TDS remains to be elucidated, the beneficial effects of GPi-DBS in patients with TDS suggest that the disease may be a basal ganglia disorder. In addition to recent advances in understanding the pathophysiology of TDS, this article introduces the current use of DBS in the treatment of medically intractable TDS.